Determination of Pb(II) by Anodic Stripping Pulse Voltammetry (ASPV) Using Platinum and Glassy Carbon Electrodes - Ramadan, A.A.; Mandal, H.; Kamel, A.A. (Asian Journal of Chemistry, 2010)
Determination of Pb(II) by Anodic Stripping Pulse Voltammetry (ASPV) in aqueous solutions of 0.01 M CH3COOH and 0.1 M NaCl using Rotating Disk platinum Electrode (RDPtE) and Rotating Disk Glassy Carbon Electrode (RDGCE) has been studied. A number of supporting types of pulses have been examined and stripping voltammetry with superimposed constant amplitude pulses of negative polarity (SVPNP) found to give the greatest sensitivity. The relative standard deviation is 5.0% at very low concentration of 4 x 10-6 M. on RDPtE. The simultaneous discharge-ionization of lead with or without 5 x 10-5 M Hg2+ has also been studied by SVPNP on RDGCE. It is shown that the sensitivity increased from 4 x 10-8 M without Hg2+ to 1 X 10-10 M with 5 x 10-5 M Hg2+. The relative standard deviations are 4.4% and 5.9% respectively. This developed method gives the possibility of determination of Pb(II) on bare RDPtE. Up to 4 X 10-6 M, the sensitivity increased from5 x 10-8 M in previous works to 1 x 10-10 M on RDGCE in presence of 5x 10-5 M Hg2+.